Effect of Mediated Learning in Teacher-Child Interactions in Urban and Rural Primary School Classrooms: An Exploratory Study - Villalta-Paucar, M (Equinox Publishing Ltd, 2021)
The objective is to analyze teacher-child interactions through Mediated Exchanges (ME) for the promotion of autonomous learning in primary education in different socio-educational contexts. We conducted a quasi-experimental study with an intervention group (IG) and control group (CG), composed of 16 teachers of students between 5 and 7 years of age, of urban and rural schools in Chile. In the IG, we implemented a feedback program. In both groups, actual classes were filmed pre and post-program, and Raven’s Colored Progressive Matrices Scale (CPM) was applied to 117 participating students. The results indicate that after the feedback, the frequency of ME in the IG increased significantly compared with the CG, in urban and rural classrooms; the children of the IG significantly increased average score ranges obtained in the CPM test. Rural and urban classrooms differed in the kind of mediated exchanges. © 2021. equinox publishing